PS-055 The incidence of drug allergies in hospitalised patients. (24th March 2015) - Vila, M; Viñas, L; Aguilar, I; Toro, C; Pérez, A; Capel, M
Abstract : Background: The literature reveals that approximately 20% of healthcare professionals fail to document drug allergies (DA) in the electronic records. Breakdowns in the documentation of allergies can lead to medicines errors (MEs). Purpose: The aims of this study were to examine patient DA profiles documented in the electronic records and to determine MEs associated with DAs. Material and methods: Retrospective observational study including all adult patients admitted to our hospital on February 24, 2014. Discharge prescriptions and patient DA profiles entered into the different (non-integrated) electronic records were reviewed. Results: 258 patients were included in the study. In all patients, a history of an allergic reaction to drugs or not was reported in at least one electronic record: 55% in the patient's admission prescriptions, 60% in the nursing consumption form and 46.4% in the electronic prescription system. Nevertheless, only in 3% of the cases was it reported in all of the records. In 13.2% of the cases, there were discrepancies between different electronic records. DAs were recorded in 60 patients. The drugs most frequently involved were penicillin (50%) and metamizole (25%). 11 MEs were identified in which a drug was prescribed for a patient with a documented DA. In 6 cases the medicine didn't reach the patient and was prevented by a pharmacist in four cases. In the other 5, the medicine reached the patients. Fortunately, there was no evidence of any reactions following the administration of the drugs. Conclusion: The existence of different non-integrated electronic records favours inadequately recorded DAs, discrepancies and MEs related to DA. Pharmacists can play an active role in getting adequate DA recording systems into hospitals and improving inpatient safety. References and/or acknowledgements: I thank Dra. Ana Pérez for helpful comments. No conflict of interest.